NPK Level in Anaerobic and Aerobic Composting Using Spoiled Rice MOL - Muliyadi, Muliyadi; Purwiningsih, Dwi Wahyu (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Nowadays in Indonesia, household waste remains the main problem. The purpose of this study is to know NPK level in anaerobic and aerobic composting using Spoiled rice MOL. This type of research is experimental, the research design is a post-test with a control group design. This type of research is experimental research design with Post-test Only Control Design. The design of this study was to determine the nitrogen, phosphorus and Potassium of compost using local microorganisms (MOL) of spoiled rice with anaerobic and aerobic composting methods. From the results of the research, the NPK content in anaerobic composting using Stale Rice MOL is 5% N, 5% P, 5% K. From the results of average measurements of temperature, pH and humidity and NPK. The temperature measurements obtained for MOL of Stale Rice are 50 ° C, 100% humidity, pH 7 and 5% N, 5% P, 5% K.